Research on Application of Photothermal Imaging Technology in Urban Rail Transit Vehicle Intelligent Operation and Maintenance - ZHANG Jianhua (Chengshi guidao jiaotong yanjiu)
［Objective］ At present, the lack of monitoring means for the operation status of key components such as axle boxes, gearboxes, and traction motors in the daily operation of urban rail transit trains, makes it impossible to realize the fault early warning and tracking of the key components, and meet the requirements of precise maintenance of the trains. To adapt to the demands of intelligent operation and maintenance technology development, it is necessary to study and solve problems of the operation status monitoring and the fault early warning of key components. ［Method］ In view of the current application status of comprehensive monitoring technology for railway vehicles, it is proposed to set up a track side comprehensive monitoring equipment of the line based on photothermal imaging technology and acoustic diagnosis to collect the temperature and noise information of the key components du-ring train operation. Dynamic monitoring and fault diagnosis of the train key components is realized by establishing a fault judgment model. ［Result & Conclusion］ Photothermal imaging technology characterizes its detection as multi-points, large coverage, strong vehicle model adaptability, accuracy, and visual results. When combined with acoustic diagnosis and other technologies, it can realize real-time monitoring and fault diagnosis for the train key component operation status, providing technical support for precise maintenance of trains.